Reprogramming monocyte-derived macrophages through caspase inhibition. (1st January 2022) - Chaintreuil, Paul; Laplane, Lucie; Esnault, Florian; Ghesquier, Victoria; Savy, Coline; Furstoss, Nathan; Arcangeli, Marie-Laure; Cluzeau, Thomas; Robert, Guillaume; Droin, Nathalie; Solary, Eric; Auberger, Patrick; et al.
ABSTRACT: Macrophages are widely distributed innate immune cells that play an indispensable role in a variety of physiologic and pathologic processes, including organ development, host defense, acute and chronic inflammation, solid and hematopoietic cancers. Beyond their inextricable role as conveyors of programmed cell death, we have previously highlighted that caspases exert non-apoptotic functions, especially during the differentiation of monocyte-derived cells in response to CSF-1. Here, we found that non-canonic cleavages of caspases, reflecting their activation, are maintained during IL-4-induced monocyte-derived macrophages polarization. Moreover, Emricasan, a pan-caspase inhibitor that demonstrated promising preclinical activity in various diseases and safely entered clinical testing for the treatment of liver failure, prevents the generation and the anti-inflammatory polarization of monocyte-derived macrophages ex vivo . Interestingly, caspase inhibition also triggered the reprogramming of monocyte-derived cells evidenced by RNA sequencing. Taken together, our findings position Emricasan as a potential alternative to current therapies for reprogramming macrophages in diseases driven by monocyte-derived macrophages.